HPV genotypes in invasive cervical cancer in Danish women. (23rd July 2013) - Kirschner, Benny; Junge, Jette; Holl, Katsiaryna; Rosenlund, Mats; Collas de Souza, Sabrina; Quint, Wim; Molijn, Anco; Jenkins, David; Schledermann, Doris
Abstract Objective Human papillomavirus (HPV) genotype distribution in invasive cervical cancers may differ by geographic region. The primary objective of this study was to estimate HPV‐genotype distribution in Danish women with a diagnosis of invasive cervical cancer. Design Observational, cross‐sectional. Population Danish data from a multi‐center study undertaken in 12 European countries. Methods A total of 342 archived fixed tissue samples with diagnosis of invasive cervical cancer from the Departments of Pathology in the University Hospitals in Hvidovre and Odense, Denmark, were anonymized and shipped to a central laboratory for histopathology review and PCR testing for HPV DNA. A standardized HPV‐test methodology was used to enable comparison of HPV‐type distribution. Main outcome measures Occurrence of HPV genotypes in Danish women with cervical cancer. Results There were 261 samples evaluated as histologically adequate and 251 (96%) of these were HPV‐positive (HPV+). The most frequent diagnosis was squamous cell carcinoma (78.9% of histological adequate and 79.3% of HPV+). Adenocarcinoma, adenosquamous carcinoma and other types were found in 14.9, 3.4 and 2.7% of the histologically adequate group and 14.7, 3.6 and 2.4% of the HPV+ group, respectively. In 92.8% of HPV+ women only a single HPV type was diagnosed. HPV‐type distribution in the latter population was as follows: HPV‐16: 62.2%; HPV‐18: 14.6%; HPV‐33: 6.9%; HPV‐45: 6.4% and HPV‐31: 3.4%. Of the HPV+ women, 6.4% were diagnosed with multiple HPV types and 0.8% had unknown HPV types. Conclusion HPV‐16 and ‐18 are detected in 74.3% of Danish women with diagnosis of invasive cervical cancer, while HPV‐16, ‐18, ‐31, ‐33, ‐45 and 58 are detected in 90.0% of women with invasive cervical disease.